Factors Influencing Energy Conservation Application in Green Campus Design Based on Green Behavior - Fachrudin, Hilma Tamiami; Fachrudin, Khaira Amalia (International Journal of Energy Economics and Policy, 2021)
The energy conservation application on campus may reduce energy consumption by using alternative energy sources. Green behavior in energy conservation by students and campus regulation has an important role in developing green campus. The purpose of this research is to analyze factors affecting energy conservation application on green campus design based on green behavior. Green behavior consists of attitudes, responsibilities, control behavior, beliefs, and intentions in energy conservation. This research used a quantitative method and conducted at universities in Medan city, Indonesia. The population of this research was university students with a total sample of 395 respondents. The analysis was carried out with SEM-PLS. Attitudes and beliefs were affecting perceived behavior control. In addition, beliefs are also affecting energy conservation application on green campus. Therefore, the campus policy and management should consider students green behavior in designing energy conservation application for green campus. Green behavior by campus occupants is beneficial to support campus efforts to apply green campus concepts. Keywords: attitude; energy conservation; green behavior; green campus design JEL Classifications: I23, P18, Q20, Q42 DOI: https://doi.org/10.32479/ijeep.11355